Optimalisasi Skrining Neuropati Perifer pada Pasien Diabetes Melitus melalui Pelatihan Kader, Keluarga, dan Pasien di Wilayah Kerja Puskesmas Mekar Baru - Novia Putri, Rima; Deliana, Muthia; Pusparianda, Dewi (Poltekes Kemenkes Tanjungpinang, 2025)
Diabetes mellitus (DM) is one of the most prevalent non-communicable diseases in Tanjungpinang City, particularly in the working area of Mekar Baru Public Health Center. The coverage of healthcare services for DM patients in this area remains low, at only 70.42%. This condition increases the risk of chronic complications such as peripheral neuropathy, which may lead to diabetic foot ulcers. In 2022, 62 cases of diabetic foot ulcers were recorded at Tanjungpinang General Hospital. This community service program aimed to enhance the knowledge and skills of health cadres, families, and DM patients in conducting peripheral neuropathy screening through education and training. The program involved the head of the health center and NCD (non-communicable disease) program coordinators as mentors, and included cadres, families, and patients as active participants. The results showed a 100% increase in participants’ knowledge and screening skills, although the increase in patient visits to health facilities reached only 10%. Future plans include integrating neuropathy screening into regular elderly Posyandu or NCD Posbindu activities every 3–6 months. This initiative is expected to strengthen the role of health cadres in the transformation of primary healthcare services and improve the quality of life of DM patients.